Access to and re-use of copyrighted materials among the students at Faculty of Law UiTM Shah Alam / Nabila Juremi … [et al.] - Juremi, Nabila; Ismail, Amirah; Abu Bakar, Nur Atikah; Mat Ziat, Nur Izzaty Zayani (2013)
This research focuses on the copyrighted materials used by the students at the Law Faculty of UiTM in which the researchers themselves are law students at UiTM Shah Alam. It has been observed that, the law students at UiTM are a group of students that come from diverse economic and social backgrounds. Regardless of their economic and social background, all these students require access to copyrighted materials such as text books, case law reports and law journals for the purpose of their study and research. This research collected data using survey as instrument to investigate the source and the type of copyrighted materials that were accessed by them, the purpose of accessing and re-using the copyrighted materials and the level of knowledge about copyright law and fair dealing exceptions. Based on the survey, it is found that the law students at UiTM need to have a clear policy which enables them to access and re-use the copyrighted materials without violating the copyright law. Therefore, it becomes the aim of this research to develop a set of policy on access to and re-use of copyrighted materials among the law students of UiTM Shah Alam. In developing the policy, this research analyzes the existing law that governs access to and re-use of copyrighted materials in Malaysia. This research is given an international outlook through a comparative study of the copyright laws in three countries which are the United Kingdom, the United States and Australia. A policy analysis has also been conducted on the policies of selected universities from these countries in order to discover the best policy model that can be proposed by this research. At the end of this research, it recommends a set of policy on access to and re-use of copyrighted materials for the students at UiTM law faculty.